2006
DOI: 10.1016/j.apmr.2006.08.326
|View full text |Cite
|
Sign up to set email alerts
|

Mental Practice With Motor Imagery: Evidence for Motor Recovery and Cortical Reorganization After Stroke

Abstract: Objectives-To measure the efficacy of a program combining mental and physical practice with the efficacy of a program composed of only constraint-induced movement therapy (CIMT) or only mental practice on stroke patients' levels of upper-extremity impairment and upper-extremity functional outcomes and to establish the relationship between changes in blood-oxygen-level dependent (BOLD) functional magnetic resonance imaging response during a specific motor or imagery task and improvement in motor function betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
125
1
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(138 citation statements)
references
References 78 publications
5
125
1
7
Order By: Relevance
“…In rehabilitation-related research, some studies have reported that physical function is improved by mental practice in stroke patients [2][3][4][5][6]19) ; however, our results showed that impaired motor imagery ability in the CVA group, suggesting that a strategy for therapeutic intervention with motor imagery is expected to have a high therapeutic effect because of the impaired attention of stroke patients. In the present study, the number of participants was too few to test reliability.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In rehabilitation-related research, some studies have reported that physical function is improved by mental practice in stroke patients [2][3][4][5][6]19) ; however, our results showed that impaired motor imagery ability in the CVA group, suggesting that a strategy for therapeutic intervention with motor imagery is expected to have a high therapeutic effect because of the impaired attention of stroke patients. In the present study, the number of participants was too few to test reliability.…”
Section: Discussioncontrasting
confidence: 56%
“…In humans, this type of injury strongly correlates with paralysis, sensory deficits, impairments in learning and memory, and disability in activities of daily living [ADL]; however, there are few effective therapies for the treatment of ischemic stroke 1) . Recent evidence suggests that the use of motor imagery training, as an additional therapy, has an effect on motor recovery after stroke [2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…A MI has therefore been widely used for training purposes, with sportsmen and musicians [Hall et al 1998, Hall 2001, Langheim et al 2002, Lotze and Halsbrand 2006, Guillot et al 2010a, and in the rehabilitation of patients who cannot perform active movements following stroke, spinal cord injury (SCI) or chronic intractable pain [Moseley 2004, Butler and Page 2006, Mulder 2007, Page et al 2009, Grangeon et al 2010, Malouin 2010. In these studies patients were verbally guided to imagine some functional, object oriented task for which they could not produce a satisfactory overt movement, such as reaching or grasping an object.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies patients were verbally guided to imagine some functional, object oriented task for which they could not produce a satisfactory overt movement, such as reaching or grasping an object. Patients achieved decreased reaching time, enhanced smoothness of a hand trajectory of their overt movements [Grangeon et al 2010], increased Fugl-Meyer score and results of the Action Research Arm (ARA) test [Page et al 2006] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation